2018
DOI: 10.1108/ijilt-08-2017-0075
|View full text |Cite
|
Sign up to set email alerts
|

Screencasting: supportive feedback for EFL remedial writing students

Abstract: Purpose The purpose of this paper is to explore screencasting as a computer-mediated feedback approach for Arabic native (L1) speakers taking an English as a foreign language (EFL) college remedial writing class. Design/methodology/approach This case study focused on an EFL remedial writing class consisting of eight Lebanese, Arabic L1 students at a private university in Lebanon. Students received screencast feedback through Jing® for one essay intended to assist them with subsequent revision. The multimodal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 34 publications
3
17
0
1
Order By: Relevance
“…An interesting aspect of this current study is the emotional component. This is consistent to what has been reported elsewhere in the literature (Ali 2016;Cranny 2016;Ghosn-Chelala and Al-Chibani 2018;Mathieson 2012). In fact, much of the literature reports that students have a positive orientation towards screencasting.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…An interesting aspect of this current study is the emotional component. This is consistent to what has been reported elsewhere in the literature (Ali 2016;Cranny 2016;Ghosn-Chelala and Al-Chibani 2018;Mathieson 2012). In fact, much of the literature reports that students have a positive orientation towards screencasting.…”
Section: Discussionsupporting
confidence: 91%
“…Most of the studies that claim screencasting is more effective than other forms of feedback, are based on self-reported measures, such as Likert-type surveys (Ghosn-Chelala and Al-Chibani 2018;Orlando 2016;Mathieson 2012;Seror 2012). Few studies were found reporting that students who have received feedback via screencasting show more improvements than a comparison group (Tekinarslan 2013; Ali 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Many believe that feedback may inform students' learning goals, performance, and strategies to improve their learning (Hattie & Timperley, 2007). Written corrective feedback on language may directly or indirectly inform necessary changes to improve students" linguistic accuracy (Biber et al, 2011;Ghosn-Chelala & Al-Chibani, 2018) and feedback on content, organization, and rhetoric may help students in making overall revision (Goldstein, 2004;Hartshorn & Evans, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Screencast feedback is a version of computer-mediated multimodal video feedback provided by a teacher (human feedback) (see Ware & Warschauer, 2006) by recording the teacher giving feedback on a digital copy of student work using a screen-capture software such as Jing, Screencast-O-Matic, and Google Meet which can record the teacher"s audio/video along with computer screen where student"s writing is seen and commented. The software also record teacher"s mouse movements, annotations, comments, highlighting, direct and indirect error correction, as well as written and verbal commentary (see Bakla, 2020;Ghosn-Chelala & Al-Chibani, 2018). Therefore, it can be positioned between written feedback and face-to-face writing conferences (Lee, 2017, p. 131).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation